DETERMINAN SOSIAL EKONOMI KEJADIAN STUNTING - Maulia Siti Mukharohmah; Mulyaningsih, Tri; Wiyono, Vincentius Hadi (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
Sragen Regency is one of the areas in Indonesia focusing on stunting alleviation. In 2018, the average prevalence of stunting children in Sragen Regency was 24.3% where this figure was higher than the average prevalence of stunting children in Central Java (20.8%) and also the national average (21.6%) (SSGI Kemenkes RI, 2022). The government has made various efforts to prevent stunting children. However, the prevalence of stunting children in Sragen Regency is still high, so policy innovations are needed to accelerate the reduction of stunting rates. This study uses primary data with data collection methods through surveys and interviews. The sampling technique used systematic random sampling; the data was then analyzed using a quantitative descriptive method and logistic regression. The study's results obtained 73 samples, of which 21 households (28.76%) had children with stunting nutritional status. The prevalence of stunting in children is higher in children whose mothers have education below junior high school, mothers who don't work, have low capita income and are children of male sex. Based on these findings, appropriate and effective interventions are needed according to the determinants of child stunting.